Amulets with Inscriptions and «Magic Squares» at the Golden Horde Settlements - Lapshin Andrey S.; Lapshina Irina Yu. (Поволжская археология)
We will talk about one rare type of finds at the Golden Horde settlements in this work. These are amulets with a «magic square» on one side and an Arabic inscription on the other. The «magic square» on such amulets is a square of the third order. It reflects Sufi magical ideas and a spirit communication by numeric and alphabetic ciphering. The second side of the amulets contains inscriptions associated with the «square» on the back. Amulets bear two inscriptions. Variants of translation are offered for each of them. As for their content they were protective prayers-dua. These finds at the settlements are connected with spread of Sufism in the cities of Golden Horde.